SCREENING OF ANTIMICROBIAL, CYTOTOXIC EFFECTS AND PHENOLIC COMPOUNDS OF THE MOSS AULACOMNIUM ANDROGYNUM (HEDW.) SCHWAGR (BRYOPHYTA) - P. Oztopcu-Vatan; F. Savaroglu; C. F. Iscen; S. Kabadere; N. Ozturk; S. Ilhan (Journal of Animal and Plant Sciences, 2017)
The second largest taxonomic group in the kingdom plantae is bryophytes, however; studies carried out to better understand their chemical composition are limited and dispersed. In this study, phenolic compounds, the antimicrobial and cytotoxic activities of different extracts from Aulacomnium androgynum (Hedw.) Schwagr. Total phenolic contents of the extracts’ were determined by Folin-Ciocalteu assay and their amount ranged from 41.79 to 98.41mg/g of gallic acid equivalents. The highest total phenolic content was obtained from ethyl acetate (C) extract. Phenolic acids in the extracts acquired by using different solvents were eluted through reversed-phase high-performance liquid chromatography, which enabled advance elution by the use of a C18 column, an acidic mobile phase, and gradient elution. Also, the most phenolic acid content was measured in the ethyl acetate extract. The antimicrobial activity of these extracts was evaluated against 6 bacterial and 7 fungal strains. Except extract D, the all extracts were active against Pseudomonas aeruginosa, and Bacillus subtilis. Acetone, petroleum ether (A) and ethyl acetate (C) extracts demonstrated inhibitory activity against Staphylococcus aureus and Enterococcus faecalis, but A and C were active against mold strains. The minimum inhibitory concentrations of the most effective extracts ranged from 93.75-375 µg/mL for the bacterial strains. The cytotoxic activity of different concentrations of methanol, A and C extracts were tested on rat glioma (C6) cells. Methanol extract decreased C6 viability in 48 hours at the concentration of 85 and 170 µg/mL. All doses of extract A stimulated C6 growth for 24 hours, but 170 µg/mL inhibited in 48 hours. IC50 value of extract C was calculated as 83 µM in 48 hours. The present study suggests the possibility that A. androgynum may possess antimicrobial and anticancer molecule(s).
Keywords: Aulacomnium androgynum; Moss; Phenolics; Antifungal; Antibacterial; Toxicity